2022
DOI: 10.3889/oamjms.2022.8211
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sleeve Gastrectomy and Mesenchymal Stem Cells Improves Insulin Resistance by Modulating Pro-inflammatory Milieu in Obese Type 2 Diabetic Rat Model

Abstract: ABSTRACT Background: Obesity is a major risk factor for the onset of insulin resistance and type 2 diabetes mellitus (T2DM) caused by chronic inflammation of the islets of langerhans. Sleeve gastrectomy (SG) procedure increases particular hormone which stimulates insulin sensitivity. Mesenchymal stem cells (MSCs) can also exhibit potential immunomodulatory properties through their paracrine effects, however the mechanism regarding combination of them could not be adequately explained.  Aim: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The high level of IL-10 expression is also in accordance with what was reported byEkasaputra et al (2022) which showed that sleeve gastrectomy…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The high level of IL-10 expression is also in accordance with what was reported byEkasaputra et al (2022) which showed that sleeve gastrectomy…”
supporting
confidence: 91%
“…The sleeve gastrectomy procedure will cause changes in the body's metabolic parameters such as an increase in the hormone Glucagon Like Peptide 1 (GLP-1) which is a hormone secreted by enteroendocrine cells in the intestine, this hormone functions to stimulate β cell growth and reduce apoptosis. GLP-1 has alternative anti-inflammatory function due to the involvement in intestinal intraepithelial lymphocytes [13].…”
Section: Discussionmentioning
confidence: 99%